The Effect of Using (Jigsaw) Strategy in Acquisition of the Scientific Concepts among Scientific’s Eleventh Class Students - Shamal Azad Abdullah; Waad M. N. Sabri (QALAAI ZANIST JOURNAL, 2021)
The objective of the research is to know (the effect of the use of the (Jigsaw) strategy in the acquisition of the scientific concepts among scientific eleventh class students). In order to verify the objective of the research, a zero hypothesis was formulated that states (that there is no statistically significant difference at )α=0.05) between the degrees of the two groups the experimental and the control groups in the acquisition of scientific concepts, and the research community was formed of all the scientific eleventh class students in the center of Erbil Governorate for the academic year (2020 - 2021) and the research sample of (54) s scientific eleventh class student in the high school (Ahmad Ismail Nanakaly) for boys, which distributed on the experimental and control groups, by (27) students of the group of studies that were taught Using the (Jigsaw) strategy and (27) students for the control group, which were taught according to the usual method. The two groups were equal in a number of variables such as: age by months, previous achievment in Biology, parent’s achievement level, intelligence and testing of the previous information. The testing of the acquisition of scientific concepts as a research tool was prepared, it has been verified the validity of the test, and the coefficient of difficulty and power discrimination of paragraphs and the effectiveness of wrong alternatives. The reliability was checked by using Cronbach's Alpha equations, reached (0.884), for the test items, and after the application of the experiment and using the appropriate statistical means, the data were analyzed The results indicated that there were statistically significant differences at the level of (α= 0.05) in the mean scores of the students of the experimental and control groups in the test of the acquisition of scientific concepts and for the benefit of the experimental group. At the end of the research, a number of recommendations and proposals were presented for future work and research.